Evaluation of Complete Blood Count Changes in Patients Undergo Hemodialysis in Shendi Town, Sudan - Mosab Nouraldein Mohammed Hamad (Middle East Research Journal of Microbiology and Biotechnology, 2024)
Background: Chronic Renal failure is a major health problem and affects the economic and social status of patients. In Sudan, according to the ministry of health records, the prevalence of renal failure is increasing by approximately 70 to 140 new patients undergoing dialysis each year. This high frequency is thought to be due to epidemic malarial infection, which is well known to cause glomerulonephritis. Methods: This is a cross-sectional descriptive study conducted in Shendi town during the period from September 2021 to January 2022, and aimed to determine hematological parameters in hemodialysis patients. A total of venous blood samples were collected in EDTA anticoagulant containers then mix well and transfer to the laboratory, following standard procedures to prevent contamination, then count complete blood count automatically. Results: Statistical analysis by SPSS showed that the Mean of HB in pre and post-hemodialysis was(7.4g/dl and7.9 g/dl), the mean PCV in pre and post-hemodialysis was(22.7% and 25.8%), the mean of RBCs count in pre and post hemodialysis was(2.6x1012cell/l and 2.8x1012cell/l), the mean of WBCs count in pre and post hemodialysis was(5.4x109/L and 5.1x109/L), the mean of platelet count in pre and post hemodialysis was(152000cell/mm3 and 146000cell/mm3), the mean of the MCV in pre and post-hemodialysis was(86.7fl and 89.0fl), the mean of MCH in pre and post-hemodialysis was(28.3pg and 28.2pg) and the mean of MCHC pre and in post hemodialysis (32.8g/dl and 31.9g/dl). Conclusion: The study concluded that the hematological parameters in Shendi town in Hemodialysis patients cause an increase in RBCs, Hb, PCV, and lymphocyte count, no significant effect on PLTs, red cell indices not affected by hemodialysis and remain within normal range and women more affected than men as well as elder people.